Theodicy and the pre-Critical Kant - Huxford, George (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This paper rests on my claim elsewhere (see Huxford, 2020) that Kant was concerned with the fundamentals of theodicy throughout his career and not just in the short 1791 essay devoted to the subject. It sets out Kant’s positions, developed in the period before the publication of his first Critique, regarding these fundamentals, namely God’s existence, the nature of evil and the reality of free will. Some of these positions were maintained through Kant’s career, others were either present only in embryonic form or abandoned altogether. Three issues dominate. First, Kant downgraded physical evil to natural harm. Second, evil was ontologically real being a negative value on the scale of goodness. Third, Kant continued to advance theoretical theodicies after the publication of his first Critique thus leaving a serious disconnect when his work is viewed in toto. I regard Kant’s thought on these fundamentals to be exploratory. So this paper does not attempt to pull his thoughts together into pre-Critical theodical “system”, although elements of such can be discerned.